Synthesis and Application of Asymmetry Diphenylketone Photoinitiators. Issue 17 (4th May 2021) - Zhao, Ziren; Song, Lu; Liu, Feng; Zhang, Bianxiang
Abstract: In this study, a series of novel functionalized benzophenone derivatives were elaborately designed and efficiently synthesized with low‐cost raw materials through a simple esterification reaction of heteroatoms/heterocycles substituted hydroxybenzophenone with acyl chloride. The chemical structures of the compounds were carefully characterized by proton nuclear magnetic resonance ( 1 H NMR), carbon nuclear magnetic resonance ( 13 C NMR), and high‐resolution mass spectrometry (HRMS). All compounds exhibited a strong and broad UV‐visible light absorption spectrum in comparison with BP. Moreover, owing to the breaking symmetry and higher molecular weight, these compounds displayed efficient photoinitiating activity and low mobility and self‐quenching as free radical photoinitiators. The resulting films exhibited much better mechanical properties compared with commercially available BP and Irgacure 184, implying potential application in industrial UV curing. Abstract : By delicately modifying the chemical structure of Benzophenone (BP), a series of benzophenone derivatives were designed and efficiently prepared by esterification reaction, which exhibited a strong and broad UV‐visible light absorption spectrum in comparison with BP. Owing to the breaking symmetry and higher molecular weight, these compounds displayed efficient photoinitiating activity and self‐quenching as free radical photoinitiators.